2013
DOI: 10.1080/10439463.2013.865736
|View full text |Cite
|
Sign up to set email alerts
|

Senior police officers' perspectives on private security: sceptics, pragmatists and embracers

Abstract: The police have traditionally been sceptical about working with some groups, and the private security sector is foremost amongst them. Arguments that there are too many negatives associated with a service that is accountable to only those who can pay can be balanced by its potential to offer more cost-effective ways of policing, not least in an austere economic climate. This article reports on interviews with police leaders about attitudes towards working with, and outsourcing functions to the private security… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…According to this perspective, policing networkstheir formation, organization and effects -are best understood as practical accomplishments that involve trust building, negotiation and compromise (see also Fleming & Wood, 2006;Rhodes, 2006). Existing research about network or partnership policing has primarily applied a police-oriented perspective to explore how police officers operate in networks and conceive of other partner agents (Gill, 2013). In this article, we argue that it is not possible to fully understand the dynamics of network policing without focusing on how private partners negotiate their relationship with the police and how they come to view the police as an (un)trustable partner.…”
Section: Introductionmentioning
confidence: 99%
“…According to this perspective, policing networkstheir formation, organization and effects -are best understood as practical accomplishments that involve trust building, negotiation and compromise (see also Fleming & Wood, 2006;Rhodes, 2006). Existing research about network or partnership policing has primarily applied a police-oriented perspective to explore how police officers operate in networks and conceive of other partner agents (Gill, 2013). In this article, we argue that it is not possible to fully understand the dynamics of network policing without focusing on how private partners negotiate their relationship with the police and how they come to view the police as an (un)trustable partner.…”
Section: Introductionmentioning
confidence: 99%
“…Studies document analyses 16 Brunet (2008) telephone interviews Brunet (2008);Gill (2013) informal field-based interviews Löfstrand Hansen (2015) focus groups Baker (2009) ;Cherney & Chui (2010) workshops Baker (2009) observations Baker (2009) ;Groenendaal & Helsloot (2015); Johnston (2003); Kerr (2012); Kruize & Gruter (2013);Löfstrand Hansen (2015); Noaks (2000Noaks ( , 2004Noaks ( , 2008; Rodas (2011);Sharp et al (2008) surveys Crawford & Lister (2006); Kruize & Gruter (2013); Lee & Yun (2014); Mopasa & Stenning (2001); Noaks (2000Noaks ( , 2004Noaks ( , 2008; Rowland & Coupe (2013) case studies 17 Topping & Byrne (2014) …”
Section: Methods Usedmentioning
confidence: 99%
“…Finally, additional policing can also lead to a raise in the security threshold whereby previously tolerated behaviour is no longer deemed acceptable, thus increasing the demand for crime control and policing interventions and heightening expectations of what these can achieve (Crawford & Lister, 2006). Some concern also exists about the risk that too heavy reliance on plural policing could lead to a twotier police service: one for those who can afford it and one for those who cannot (Crawford & Lister, 2006;Gill, 2013). What is more, one study found that some respondents believed that the perception that a two-tier system might occur could undermine effective police work (Gill, 2013).…”
Section: Potential Negative Consequences Of Plural Policingmentioning
confidence: 99%
See 2 more Smart Citations